Military Deterrence vs Foreign Interference? Record of the Cold War - I. A. Istomin (Vestnik MGIMO-Universiteta)
Academic literature is largely skeptical regarding the role of military deterrence in addressing low-level coercion. The stability-instability paradox suggests that increasing destructiveness of the armed forces (especially with the emergence of nuclear weapons) diminishes their utility in response to limited wars, proxy conflicts or economic sanctions. Recent debates often extend the same logic to foreign interference in internal affairs, as they position it as a supplement for forcible rivalries. This article seeks to advance understanding of the linkage between military deterrence and foreign interference in internal politics by exploring the record of the early Cold War starting from 1948 to the mid-1950s. The analysis attests that concern over the Soviet military capabilities had a major restraining effect on Washington. As a result, the US pursued more cautious activities against the Soviet Union in comparison to the campaigns targeting less capable states. This historical record reveals that interference is more amenable to military deterrence than other types of low-level coercion. It differs from them, as covert operations produce an existential danger to the political leaders of a target state, inciting overreaction on their behalf. Therefore, they create escalation risks when threatening a great power. Interference exacerbates confrontation even between adversaries that perceived each other as malign beforehand. Apart from signaling hostile intentions, it aggravates a sense of urgency on finding a response. Although military capabilities do not provide a direct solution to political threats, they serve as a repellent against potential subversive activities. These conclusions do not depend on the specific type of interference pursued by external agents. The findings of the article demonstrate that cross-domain deterrence is more prevalent than stability-instability paradox envisages.